Ubuntu as a Dramaturgical Tool for Building Community in Protests - Refiloe Lepere; Tebogo Radebe (E-Journal of Humanities, Arts and Social Sciences)
In this paper, ubuntu is proposed as a dramaturgical lens for analysing social phenomena, particularly focusing on the 2015 Wits Student Protest (#FeesMustFall). The purpose of this study was to explore how ubuntu, as an epistemological and dramaturgical tool, can deepen the understanding of protest and community dynamics through performance. Methodologically, dramaturgy of everyday life framework is used to analyse the songs sung during the #FeesMustFall protest, emphasising their role in shaping political agency and fostering community. Songs analysed are “Jikijela” by Letta Mbulu, along with its reworked version by Thandiswa Mazwai, the decolonised “Nkosi Sikelela iAfrika,” and the title song from Mbongeni Ngema’s play Asinamali. The findings suggest that ubuntu provides an alternative epistemic lens, challenging traditional views of protest as primarily destructive. Instead, through shared performance and song, ubuntu fosters collective identity and democratic participation. The argument posited is that embodiment of ubuntu during protests creates space for community negotiation and self-actualisation, redefining the narrative of democratic agency in protest. This study contributes to scholarship by offering a new framework for understanding the role of songs in protests as dramaturgical tools that create roles, scripts, and shared experiences. Ubuntu as a dramaturgical lens expands the possibilities for analysing social movements and highlights the transformative power of performance in building communities.